Characterization of minerals, metals, and materials 2015 : proceedings of a symposium sponsored by the Materials Characterization Committee of the Extraction and Processing Division of the Minerals, Metals & Materials Society (TMS) held during TMS 2015, 144th Annual Meeting & Exhibition, March 15-19, 2015, Walt Disney World, Orlando, Florida, USA - Carpenter, John S.; Bai, Chen-Guang; Escobedo, Juan Pablo, 1978-; Hwang, Jiann-Yang; Ikhmayies, Shadia J.; Li, Bowen (Materials scientist); Li, Jian (Materials scientist); Monteiro, Sergio Neves; Peng, Zhiwei; Zhang, Mingming (Metallurgist) (Springer, 2016)
This collection focuses on the characterization of minerals, metals, and materials as well as the application of characterization results on the processing of these materials. Papers cover topics such as clays, ceramics, composites, ferrous metals, non-ferrous metals, minerals, electronic materials, magnetic materials, environmental materials, advanced materials, and soft materials. In addition, papers covering materials extraction, materials processing, corrosion, welding, solidification, and method development are included. This book provides a current snapshot of characterization in materials science and its role in validating, informing, and driving current theories in the field of materials science. This volume will serve the dual purpose of furnishing a broad introduction of the field to novices while simultaneously serving to keep subject matter experts up-to-date.
Included indexes.
Keywords: Materials -- Testing -- Congresses.; Materials -- Analysis -- Congresses.; Minerals -- Congresses.; Materials science -- Congresses.; Metallography -- Congresses.; Physical metallurgy -- Congresses.; Materials science.; Metals.; Ceramics.; Glass.; Composite materials.; elektronické knihy; electronic books